The relationship between instrumental and transformative learning in structured workplace learning programs: Insights from embedded formative assessment - Cheryl K Baldwin (Adult Education Research Conference, 2016)
A grounded theory study of tacit knowledge elicited in workplace learning programs examined instrumental and transformative elements. Observational, reflective and interview data indicated that learner beliefs about work challenged content legitimacy. Low levels of reflective dialogue were associated with immediate application or quieting reactions. Instrumental content helped prompt perspective shifts.
Keywords: Transformative learning; instrumental workplace goals